MANAJEMEN KRISIS PERSPEKTIF AL-QUR'AN DAN HADIS - Rahayu, Sri; Ahmadi, Ahmadi; Hidayati, Noorazmah (Berajah Journal, 2024)
This article discusses the concept of crisis management in Islam through analysis of hadith with sanad and matan as well as support from verses from the Koran. The hadith which says, "Allah loves those who do a job, does it with itqan (precise, directed, clear, complete)" (HR. Thabrani) is used as the main basis, showing the importance of thoroughness and sincerity in carrying out tasks, especially in crisis situations. Apart from that, the Al-Qur'an provides guidance on business and careful planning in dealing with crises, as stated in Surah Al-Mulk verse 15. The story of the Prophet Yusuf in the Al-Qur'an is also raised as a real example of risk management and mitigation strategies. effective crisis. This article concludes that the principles taught in the hadith and the Qur'an can be applied in modern crisis management, emphasizing the values of sincerity, perseverance, and careful planning as keys to dealing wisely and effectively with emergency situations.